Doppler evaluation of renal blood flow as a predictive index of acute renal failure in perinatal asphyxia - Viraraghavan Vadakkencherry Ramaswamy; Arvind Saili; Rama Anand; Sushma Nangia (Hygeia Press di Corridori Marinella, 2019)
Background: Renal involvement is a common occurrence in perinatal asphyxia. Till date, only a handful of studies from across the globe have evaluated the use of renal Doppler as a predictive modality for acute kidney injury (AKI) in birth asphyxia. Aims: To evaluate the role of Doppler study of renal blood flow in predicting acute renal failure in perinatal asphyxia. Settings and design: This was a prospective cohort study. Materials and methods: 30 preterm and term neonates with perinatal asphyxia defined as an Apgar score of 0-3 at 1 minute and cord pH of ≤ 7.00 or base deficit of > 16 mmol/L and 30 healthy neonates matched for gestational and postnatal age were enrolled. Renal blood flow parameters were studied on the 1st day and the 3rd day. Serum creatinine was taken as the gold standard for defining AKI. Statistical analysis used: Receiver operating characteristics (ROC) was used to evaluate the diagnostic performance of renal Doppler. SPSS® version 17.0 was used. Results: The ROC curves obtained for all the renal blood flow parameters on day 1 and day 3 to see the utility of the renal Doppler ultrasonography in predicting acute renal failure in severe birth asphyxia revealed that the area under the curve (AUC) was not significant for any of the parameters. Conclusions: Contrary to the results seen in the previous studies, this study indicates that renal blood flow parameters may not be a useful modality to predict the occurrence of AKI in perinatal asphyxia.